Pengaruh Promosi Penjualan, Word Of Mouth, Dan Citra Merek Terhadap Keputusan Pengguna Jasa Dalam Menggunakan Grab Di Kota Bogor - Saputra, Damianus Yobellio Resmi; Pratomo, Anton Widio (Jurnal Aplikasi Bisnis Kesatuan, 2023)
Transportation is one field that is progressing and development. One online transportation company that is experiencing development and progress is Grab. This study aims to (1) Determine the effect of Sales Promotion on Consumer Decisions (2) Determine the effect of Word of Mouth on Consumer Decisions (3) Determine the effect of Brand Image on Consumer Decisions (4) Determine the effect of Sales Promotion, Word of Mouth, and Brand Image on Consumer Decisions. This sample method uses non-probability sampling with a purposive sampling type with sample calculations using the Cohcran formula. The number of respondents selected was 385 people who were Grab service users. The research data was processed using SPSS 23 software. The results of the analysis show that partially (1) there is a positive and significant relationship between Sales Promotion and Consumer Decisions. (2) There is a positive and significant relationship between word of mouth and consumer decisions. (3) There is a positive and significant relationship between Brand Image and Consumer Decisions. (4) Sales Promotion, Word of Mouth, and Brand Image together have a positive and significant effect on Consumer Decisions. Keywords : Sales Promotion, Word of Mouth, Brand Image